2016
DOI: 10.1534/g3.115.025858
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Extrachromosomal Circular DNA from Long Terminal Repeats of Retrotransposons inSaccharomyces cerevisiae

Abstract: Extrachromosomal circular DNA (eccDNA) derived from chromosomal Ty retrotransposons in yeast can be generated in multiple ways. Ty eccDNA can arise from the circularization of extrachromosomal linear DNA during the transpositional life cycle of retrotransposons, or from circularization of genomic Ty DNA. Circularization may happen through nonhomologous end-joining (NHEJ) of long terminal repeats (LTRs) flanking Ty elements, by Ty autointegration, or by LTR–LTR recombination. By performing an in-depth investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
47
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 75 publications
5
47
1
Order By: Relevance
“…In summary, we have previously shown that circular DNAs are generated from genomic copies of yeast transposable elements 7 . It is currently unknown to which extent this is happening in mammalian genomes rich in transposable element sequences.…”
Section: Implications Of Dna Circularization By Human Transposable Elmentioning
confidence: 93%
See 4 more Smart Citations
“…In summary, we have previously shown that circular DNAs are generated from genomic copies of yeast transposable elements 7 . It is currently unknown to which extent this is happening in mammalian genomes rich in transposable element sequences.…”
Section: Implications Of Dna Circularization By Human Transposable Elmentioning
confidence: 93%
“…If nucleotide differences exist between the 2 LTR sequences flanking an element the apparent breakpoint site can be inferred, 5 and any apparent breakpoints outside the transcription start site region are therefore inconsistent with circles generated through circularization of linear extra-chromosomal DNA. Although only a few LTR sequences contained informative nucleotide differences, all tested sequences were inconsistent with being generated through circularization of linear extra-chromosomal DNA 7 . It therefore seems that yeast LTR elements are a source for circular DNAs through genomic recombination between the flanking LTR sequences.…”
mentioning
confidence: 97%
See 3 more Smart Citations